On blockchain and its integration with IoT. Challenges and opportunities - Reyna, Ana; Martín-Fernández, Cristian; Chen, Jaime; Soler-Castillo, Enrique; Díaz-Rodríguez, Manuel (Elsevier, 2018)
In the Internet of Things (IoT) vision, conventional devices become smart and autonomous. This vision is turning into a reality thanks to advances in technology, but there are still challenges to address, particularly in the security domain e.g., data reliability. Taking into account the predicted evolution of the IoT in the coming years, it is necessary to provide confidence in this huge incoming information source. Blockchain has emerged as a key technology that will transform the way in which we share information. Building trust in distributed environments without the need for authorities is a technological advance that has the potential to change many industries, the IoT among them. Disruptive technologies such as big data and cloud computing have been leveraged by IoT to overcome its limitations since its conception, and we think blockchain will be one of the next ones. This paper focuses on this relationship, investigates challenges in blockchain IoT applications, and surveys the most relevant work in order to analyze how blockchain could potentially improve the IoT.
Keywords: Internet de los objetos; Internet of Things; Blockchain; Smart contract; Trust